MANAJEMEN SUPERVISI AKADEMIK KEPALA MADRASAH DALAM MENINGKATKAN KINERJA GURU DI MI MABDAUL ULUM - Sholihah, Imro'atus (LP2M STAI AL-UTSMANI BONDOWOSO, 2022)
Article this aims to knowing the academic supervision management of madrasah principals in improving teacher performance at Madrasah Ibtidaiyah Mabdaul Ulum. So the research wants to know the efforts and problems of the academic section in improving teacher performance, especially in planning, organizing, implementing and evaluating. The method used by the researcher is a qualitative method, while the which used is Approach Qualitative Descriptive . Technique data collection is observation, interviews, and documentation. Whereas technical analysis data use Triangulation Source and Technique. So that h results research is to breastfeed in the new school year and include teachers. This academic supervision program is structured based on the problems faced by teachers regarding learning problems and adjusts the needs of teachers. The implementation of academic supervision has been planned in accordance with supervision techniques including group supervision and individual supervision. Evaluation is seen from the planning and implementation of academic supervision programs that are implemented and follow-up actions follow up on what the madrasa principal does by providing coaching or training to teacher which not yet Fulfill standard as well as appreciation on teacher which meet the standards and factors supporting and inhibiting academic supervision head master. Based on the results of these studies, the implementation of academic supervision management of madrasah principals in improving teacher performance in Madrasah Ibtidaiyah Mabdaul Ulum not yet done with good in enhancement teacher performance.